ANALISIS KEBUTUHAN PENGEMBANGAN INSTRUMEN PENILAIAN LITERASI DIGITAL BERBASIS CHATBOT JENJANG SMP PADA PEMBELAJARAN IPS MATERI MOBILITAS SOSIAL - Evitawati, Geovanny; Sarwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of artificial intelligence technology, particularly chatbots, has created new opportunities for innovation in education. This study aims to analyze the need for developing a chatbot-based assessment instrument in the context of Social Studies (IPS) learning, focusing on the topic of Social Mobility for junior high school students. The research employed a need analysis approach as the initial phase of the research and development (R&D) model. Data were collected through literature review, preliminary observation, and field interviews at SMP Negeri 1 Pabelan, Semarang Regency. The findings indicate a high level of interest from both teachers and students regarding chatbot integration; however, teachers’ technical and pedagogical understanding remains limited. Thus, a valid and reliable assessment instrument is needed to evaluate teachers’ digital literacy competencies in utilizing chatbots. This instrument is expected to serve as a diagnostic tool and as the foundation for targeted and contextual digital literacy training. The study contributes to the initial stage of developing relevant educational instruments in response to the demands of the digital era.